Differential induction of plasma cells by isoforms of human TACI - Garcia-Carmona, Yolanda; Cols, Montserrat; Ting, Adrian T.; Radigan, Lin; Yuk, Frank J.; Zhang, Li; Cerutti, Andrea; Cunningham-Rundles, Charlotte (Blood, 2015)
Subjects with common variable immune deficiency may have mutations in transmembrane activator calcium modulator and cyclophilin ligand interactor (TACI). Unlike the murine gene, human TACI undergoes alternative messenger (m)RNA splicing to produce isoforms with 1 or 2 ligand-binding domains. Because both isoforms are found in human B cells, we compared their functions in transduced murine B and human pre-B cells. Although murine cells and pre-B cells transduced with the long TACI isoform retained surface CD19 and immunoglobulin G, cells transduced with the short TACI isoform completely lost these B-cell characteristics. Expression of the short TACI isoform produced intense nuclear factor κB activation, nuclear p65 translocation, and colocalization with myeloid differentiation factor 88 and calcium-modulating cyclophilin ligand. The short TACI–transduced cells became larger and CD138 positive, demonstrated upregulated BLIMP1 and XBP1 mRNA, and acquired the morphology of plasma cells. In contrast, cells bearing the long isoform had significantly less BLIMP1 and XBP1 mRNA and, for human pre-B cells, remained CD138 negative. Although human B cells express both isoforms, the short isoform predominates in CD27+ B cells, toll-like receptor 9–activated peripheral B cells, and splenic marginal zone B cells. Although the transcriptional controls for alternative splicing of isoforms remain unknown, differential signals via isoforms may control plasma-cell generation in humans. •Activation of TACI on B cells leads to proliferation, isotype switch, and B-cell survival.•Human TACI is produced in 2 isoforms; only the short form is a potent inducer of plasma-cell differentiation.